2010
DOI: 10.1007/s10735-010-9265-7
|View full text |Cite
|
Sign up to set email alerts
|

Broad tissue expression of membrane progesterone receptor Alpha in normal mice

Abstract: The broad tissue distribution of membrane progesterone receptor alpha (mPRalpha) in vertebrates suggests multiple physiological functions of the receptor. Current knowledge regarding the receptor distribution, however, is largely obtained via non-histological assays. In this study, the tissue distribution of mPRalpha in mice of both sexes was described using both histological and non-histological methods. Immunohistochemical analysis revealed that abundant expression of mPRalpha was consistently detected in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…mPR␣ MEDIATES P4 UPREGULATION OF NO SYNTHESIS mPR mediating nongenomic progesterone actions in many reproductive and nonreproductive tissues (12,59), and similarly to the current results, mPR␣ is highly expressed on the plasma membranes of murine vascular endothelial cells (72). However, mPR␤ is frequently coexpressed with mPR␣ (10,11) and is a partner in mediating membrane receptor binding and physiological functions of progesterone in diverse cell types, including human myometrial cells (23), a GnRH neuronal cell line (59), breast cancer cells (44), and fish oocytes (66).…”
Section: E907supporting
confidence: 88%
“…mPR␣ MEDIATES P4 UPREGULATION OF NO SYNTHESIS mPR mediating nongenomic progesterone actions in many reproductive and nonreproductive tissues (12,59), and similarly to the current results, mPR␣ is highly expressed on the plasma membranes of murine vascular endothelial cells (72). However, mPR␤ is frequently coexpressed with mPR␣ (10,11) and is a partner in mediating membrane receptor binding and physiological functions of progesterone in diverse cell types, including human myometrial cells (23), a GnRH neuronal cell line (59), breast cancer cells (44), and fish oocytes (66).…”
Section: E907supporting
confidence: 88%
“…Recently we showed that the mammary ducts of normal mice were positive for both PR and mPRα. The PR was predominantly seen in the ductal epithelium, while mPRα was mostly observed in the basal myoepithelial cells [22]. The synergistic roles of mPRα and PR in normal mammary glands remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The color was developed with the ImmPACT DAB kit (VECTOR Lab, Burlingame, CA, USA). Between the incubations, the slides were washed twice with 1× PBS buffer (5 minutes each) [19,22]. Two negative controls were included: (1) control slides were stained without the primary antibody; (2) control slides were incubated with a specific blocking peptide (cat# sc-50111p, Santa Cruz, CA, USA) prior to the primary antibody incubations.…”
Section: Methodsmentioning
confidence: 99%
“…mPRs were discovered in teleost ovaries (Zhu et al, 2003b) and subsequently identified in sheep, pig, mouse, rat and human (Aparicio et al, 2011;Dressing et al, 2011;Qiu et al, 2008;Thomas et al, 2007;You et al, 2010;Zhu et al, 2003a).…”
Section: Mprsmentioning
confidence: 99%